Mother of bliss : Ānandamayī Mā (1896-1982) - Hallstrom, Lisa Lassell (Oxford University Press, 1999)
1. Introduction. 2. The Life Story of Anandamayi Ma. 3. Woman. 4. Saint. 5. Guru. 6. Avatara and Divine Mother. 7. Anandamayi Ma and Gender. Bibliography. Index.